Awareness of Malaysian Towards 3D Printed Healthcare Products - Chin , Lu Tong; Lee, Te Chuan (Research in Management of Technology and Business, 2025)
3D printing is an emerging additive manufacturing technology in Malaysia's healthcare industry. However, there are some problems, such as the critical global organ shortage crisis, challenges in 3D-printed applications in healthcare, and the lack of studies on Malaysians' awareness of 3D printing in the medical field. The objectives of this study were (1) to measure the level of Malaysian awareness of 3D-printed applications in healthcare and (2) to investigate the relationship between perceived benefits, knowledge of 3D printing, and attitudes towards Malaysian awareness of 3D-printed applications in healthcare. This study was conducted using quantitative methods, where questionnaires were used to collect the data. Random sampling was applied. The targeted number of respondents in this study was 120, and the data was gathered using a questionnaire and quantitatively evaluated using SPSS software. The findings of this research show that there is a high level of awareness among Malaysians regarding 3D-printed applications in healthcare, with an average mean score of 3.588. All the variables showed a positive impact on Malaysians' awareness of 3D-printed applications in healthcare, with attitude having the highest impact (Spearman’s correlation coefficient value of 0.839, p = 0.000), followed by knowledge of 3D printing (Spearman’s correlation coefficient value of 0.782, p = 0.000) and perceived benefits (Spearman’s correlation coefficient value of 0.774, p = 0.000). Consequently, there were several expected advantages from this study on the awareness of 3D-printed applications in healthcare: patients would have a higher quality of life, doctors would be able to work more efficiently, and researchers would be able to make technological breakthroughs.